ANALISIS PERILAKU BELAJAR MAHASISWA DALAM PENGGUNAAN E-LEARNING MATA KULIAH BAHASA INDONESIA - Laila Fitri Nur Hidayah (Kantor Bahasa Provinsi Maluku Utara, 2022)
Technological advances in learning are expected to help students and lecturers. This study examines how student learning behavior in the application of e-learning in Indonesian language courses? What are the obstacles and solutions in implementing e-learning for Indonesian language courses? The purpose of this study was to determine student learning behavior in the application of e-learning Indonesian courses and find solutions to the problem of implementing e-learning Indonesian courses. The method used is a combination method by combining quantitative and qualitative research methods. Samples were taken as many as 60 of the population of all students who took Indonesian language courses at the Faculty of Islamic Religion, Nahdlatul Ulama University, Surakarta. Data collection techniques used are questionnaires through Google Forms and interviews. The analysis was carried out using the SPSS program and descriptive. The results of this study revealed that the average student felt the impact of e-learning learning on student learning behavior was good. However, it needs to be re-evaluated so that the positive impact can be greater. In addition, there are still students who answer that they have less impact, which is enough to be a record of the e-learning learning that has been running. There are several obstacles in the implementation of e-learning in the first year. However, with the solutions provided, it can be overcome immediately and make e-learning learning as good and even better than face-to-face learning.